Bedside to bench Alport syndrome research: are human urine‐derived podocytes the answer?†. Issue 1 (23rd October 2020) - Kim, Jin‐Ju; Fornoni, Alessia
Abstract: In a recent issue of The Journal of Pathology, Iampietro et al isolated and characterized several clones of urine‐derived podocytes from three patients with Alport syndrome (AS) and proteinuria and one age‐matched non‐proteinuric control. They reported differential expression of genes involved in cell motility, adhesion, survival, and angiogenesis. The authors found AS podocytes to be less motile and to have significantly higher permeability to albumin compared to control podocytes, highlighting that AS podocytes may retain their phenotype even when losing contact with the glomerular basement membrane. The establishment of urine‐derived podocyte cell lines from patients with different genetic forms of AS may represent a valuable and minimally invasive tool to investigate the cellular mechanisms contributing to kidney disease progression in AS and may allow for the establishment of patient‐specific drug screening opportunities. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.